2016
DOI: 10.4236/health.2016.82021
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Physical Exercise among Jordanians with Diabetes Mellitus

Abstract: This study is aimed to investigate exercise behaviors (frequency and duration) among Jordanian diabetic patients, and their correlation with their physical characteristics and perceived exercise benefits and barriers, exercise self efficacy, and exercise planning. An exploratory descriptive design was utilized using the cross-sectional survey with self-reported questionnaires (Demographics, Charlson Comorbidity Index, Exercise Self-Efficacy Scale, Exercise Benefits and Barriers Scale, and Commitment to a Plan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…A total of 32 studies were eligible and included in this review focusing on the barriers to good glycemic control and adherence to diabetes management plan in adults with T2DM in Jordan. Of these 32 studies, 13 discussed issues related to Type 1 diabetes and T2DM,8,14–16,31,35,42,43,53–57,71 while 13 focused on T2DM only 10,11,17,19,21,25,29,33,34,44,45,48,56. Four of the studies addressed other long-term diseases alongside diabetes,26,50,51,70 and two studies focused on lifestyle issues and diabetes-risk factors 18,41.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 32 studies were eligible and included in this review focusing on the barriers to good glycemic control and adherence to diabetes management plan in adults with T2DM in Jordan. Of these 32 studies, 13 discussed issues related to Type 1 diabetes and T2DM,8,14–16,31,35,42,43,53–57,71 while 13 focused on T2DM only 10,11,17,19,21,25,29,33,34,44,45,48,56. Four of the studies addressed other long-term diseases alongside diabetes,26,50,51,70 and two studies focused on lifestyle issues and diabetes-risk factors 18,41.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the publication of research findings that have shown the importance of physical activity, the recommended physical activity among patients with diabetes in Jordan is still low. Low levels of physical activity are reported as being common among patients with poorly controlled diabetes 10,11,42. A cross-sectional study revealed that 51 (45.1%) patients reported walking as the most common exercise and lack of desire, time, and having diabetes were reasons for not exercising 42…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several Jordanian studies indicated that patients adhered poorly to healthcare recommendations about physical exercise (Darawad et al 2014;Khalil et al 2013;Mosleh & Darawad 2015). In general, the Jordanian population is not physically active and does not consider physical exercise as a part of their daily routine (Al-Nsour et al 2012;Darawad et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the advantages of performing physical exercise for patients with chronic diseases are well-documented, their adherence to exercise recommendations is still less than the required (Hammad, Darawad, Haourani, & Demeh, 2015;Laoutaris et al, 2007). For instance, Darawad, Mosleh, et al (2016) reported that patients with DM exercised for an average of only 2.9 hr weekly, which was less than the recommended for such group of patients.…”
Section: Introductionmentioning
confidence: 99%